Application of Diversion in Investigating Child Cases - Ari Saputra (Ius Poenale, 2020)
Inversion instrument that is applied in the community in addition to providing benefits, but does not rule out there are also weaknesses. So far, diversion policies are still very little carried out in the regions even though diversion is mandatory. In the juvenile justice system, of course, children get specificity about the investigator. Whereas those who have the right to investigate children are investigators who have experience and dedication for children, because the diversion is not as easy as imagined in its implementation, especially in remote areas. As for the focus in writing this journal is how the policy of application of diversion in the investigation of cases of children and what the impact or consequences of diversion in order to provide the rights of children who are in conflict with the law. The method used in this paper is a method with a juridical approach to Empirical and Normative Juridical. Based on the results of research and discussion, it can be seen that the effectiveness of the policy of diversion of investigators in order to save the future of children is actually far from effective in the field because it is not easy to implement the diversion. The facts on the ground that the implementation of diversion still has technical constraints such as the difficulty of victims signing a peace agreement as one of the non-juridical conditions that has been required in the diversion, so that the implementation of the diversion failed to do. Lack of understanding from the public about diversion, this has the potential to cause public complaints from the public, and the impact or legal consequences of diversion that can avoid bad stigmatization of children and be able to provide alternative solutions in the form of criminal penalties because the function of diversion is to provide a win-win solution. Based on the description above, the writer's suggestion is: It is better for the National Police to be more effective in carrying out diversionary efforts to children who are dealing with the law so that the image of police law enforcement does not prioritize punishment alone but rather seeks a win-win solution for children. The victim should eliminate the egocentric and vengeful attitude towards the suspect child so that the diversion can be carried out properly.